Safety of transrectal ultrasound-guided prostate biopsy in patients receiving aspirin: An update meta-analysis including 3373 patients. Issue 34 (27th August 2021) - Chen, Di; Liu, Gang; Xie, Yurun; Chen, Changsheng; Luo, Zhihua; Liu, Yujun
Abstract: Background: The management of aspirin before transrectal prostate puncture-guided biopsy continues to be controversial. The conclusions in newly published studies differ from the published guideline. Therefore, an updated meta-analysis was performed to assess the safety of continuing to take aspirin when undergoing a transrectal ultrasound-guided prostate biopsy (TRUS-PB). Methods: We searched the following databases for relevant literature from their inception to October 30, 2020: PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Medline, Web of Science, Sinomed, Chinese National Knowledge Internet, and WANGFANG. Studies that compared the bleeding rates between aspirin that took aspirin and non-aspirin groups were included. The quality of all included studies was evaluated using the Newcastle-Ottawa Scale. Revman Manger version 5.2 software was employed to complete the meta-analysis to assess the risk of hematuria, hematospermia, and rectal bleeding. Results: Six articles involving 3373 patients were included in this meta-analysis. Our study revealed that compared with the non-aspirin group, those taking aspirin exhibited a higher risk of rectal bleeding after TRUS-PB (risk ratio [RR] = 1.27, 95% confidence interval [CI] [1.09–1.49], P = .002). Also, the meta-analysis results did not reveal any significant difference between the 2 groups for the risk of hematuria (RR = 1.02, 95%CI [0.91–1.16], P = .71) and hematospermia (RR = 0.93, 95%CI [0.82–1.06], P = .29). Conclusion: Taking aspirin does not increase the risk of hematuria and hematospermia after TRUS-PB. However, the risk of rectal bleeding, which was slight and self-limiting, did increase. We concluded that it was not necessary to stop taking aspirin before undergoing TRUS-PB.